Hypoxia-inducible factor in breast cancer: role and target for breast cancer treatment - Zhi, Shijiao; Chen, Chen; Huang, Hanlin; Zhang, Zhengfu; Zeng, Fancai; Zhang, Shujun (Frontiers in Immunology, 2024)
Globally, breast cancer stands as the most prevalent form of cancer among women. The tumor microenvironment of breast cancer often exhibits hypoxia. Hypoxia-inducible factor 1-alpha, a transcription factor, is found to be overexpressed and activated in breast cancer, playing a pivotal role in the anoxic microenvironment by mediating a series of reactions. Hypoxia-inducible factor 1-alpha is involved in regulating downstream pathways and target genes, which are crucial in hypoxic conditions, including glycolysis, angiogenesis, and metastasis. These processes significantly contribute to breast cancer progression by managing cancer-related activities linked to tumor invasion, metastasis, immune evasion, and drug resistance, resulting in poor prognosis for patients. Consequently, there is a significant interest in Hypoxia-inducible factor 1-alpha as a potential target for cancer therapy. Presently, research on drugs targeting Hypoxia-inducible factor 1-alpha is predominantly in the preclinical phase, highlighting the need for an in-depth understanding of HIF-1α and its regulatory pathway. It is anticipated that the future will see the introduction of effective HIF-1α inhibitors into clinical trials, offering new hope for breast cancer patients. Therefore, this review focuses on the structure and function of HIF-1α, its role in advancing breast cancer, and strategies to combat HIF-1α-dependent drug resistance, underlining its therapeutic potential.